Validation of suitable reference microRNAs for qRT-PCR in Osmanthus fragrans under abiotic stress, hormone and metal ion treatments - Zhang, Yingting; Yan, Qingyu; Xia, Hui; Yang, Jie; Zeng, Xiangling; Li, Zeqing; Cai, Xuan; Zou, Jingjing; Chen, Hongguo (Frontiers in Plant Science, 2025)
IntroductionSweet osmanthus (Osmanthus fragrans) is a prominent woody ornamental plant extensively utilized in horticulture, the food industry, cosmetics, and traditional Chinese medicine. MicroRNAs (miRNAs) are crucial regulators of gene regulation, playing a vital role in enabling plants to adapt to environmental fluctuations. Despite their significance, research on miRNA expression in O. fragrans under adverse stress conditions remains limited. Therefore, the selection of appropriate reference miRNAs is essential to ensure accurate miRNA expression analysis.MethodsIn this study, qRT-PCR technology was combined with four algorithms (i.e., delta-Ct, geNorm, NormFinder, and BestKeeper) to systematically evaluate the expression stability of 14 candidate miRNAs across eleven environmental conditions, including under abiotic stress, under hormone and metal ion treatments, during flower opening and senescence, and across various tissues.ResultsThe results revealed that under hormone treatments, ofr-miR159b-3p, novel8, and novel3 exhibited high expression stability; under abiotic stress, ofr-miR159b-3p, novel8, ofr-miR403-3p, and novel2 demonstrated considerable stability; during metal ion treatments, novel3, ofr-miR159b-3p, novel33, novel2, and ofr-miR395e were identified as stable miRNAs; in different tissues, novel2 and ofr-miR395e were relatively stable; and during flower opening and senescence, novel33 and ofr-miR395e maintained stable expression.DiscussionThis study represents the first comprehensive assessment of reference miRNA stability in O. fragrans, providing a reliable framework for miRNA expression analysis under diverse conditions, including flower development and senescence, abiotic stress, hormone treatments, and metal ion treatments. These findings carry significant implications for future research into the function of miRNAs.